O impacto da educação no combate à pobreza no Brasil - Sousa, Adilson Reis Pinto de (2010)
The present study intends to investigate the relationship between education and poverty in Brazilian's states for the period comprehended between 1995 and 2007. As such, we used as methodology the estimation of two econometric models for panel data, which took the poverty level as the dependent variable and the level of education, a dummy for Northeast states and control variables as independent variables. The control variables chosen were participation of rural sector in total GDP and time. To measure the level of education we used in a first model the average years of schooling and in a second model the number of literate citizens per state. The results of the estimation of both models using random effects suggest that the level of education was negatively related with the poverty level during the period. Moreover, the poverty level in Northeast has shown to be greater than in the rest of Brazil, every thing else held constant. Regarding the model that uses the number of literate as proxy to the level of education, we observe a reduction of the poverty level in Brazilian's states for the sample period and that the states with greater participation of the rural sector in it’s GDP showed greater poverty level.